A ghost in the salt: A new species of halotolerant tube-web spider in the genus Ariadna (Araneae: Segestriidae) - Marsh, Jessica R.; Hudson, Peter; Framenau, Volker W. (Zootaxa, 2021)
A new species of halotolerant Ariadna Audouin, 1826 is described from Western Australia, based on morphological features of both the male and female, and elevating the total number of described species of Ariadna in Australia to 14. This is the first record of the tube-web spider family Segestriidae Simon, 1893 inhabiting salt lakes, where they construct burrows in to the lake surface. The species is likely to be of conservation importance, due to its specialised habitat requirements and the many threats posed to the salt lake ecosystem. We provide recommendation for Ariadna phantasma sp. nov. to be considered for inclusion in the IUCN Red List.